The effect of chiropractic manual manipulation of the cervical spine on fist acceleration in boxers - Morelli, S. (Faculty of Health Sciences, University of Johannesburg, 2020)
In boxing, fist acceleration is important for delivering large volumes of blows, hard punches and blocking opponent attacks, all factors being important for victory in fights. Regardless, there is very little knowledge on the effects of chiropractic manual manipulation of the cervical spine on fist acceleration, punch force or punch frequency. This problem was further compounded by varying and contrasting views on the effects of spinal manipulative therapies on athletes` performance. For the purposes of this study, the term `fist acceleration` encompasses 3 aspects; namely: `punch acceleration`, `punch force`, and `punch frequency`. Aim: The aim of the study was to test the effects of chiropractic manual manipulation of the cervical spine on left- and right-hand fist acceleration among amateur boxers. Method: Two groups of fifteen participants each consisting of males and females between the ages of 20 and 37 years were sampled. The first group (group 1) received chiropractic manual manipulation of the cervical spine as a treatment and the second group only a short rest. The performance of both groups was measured using a micro-electrical-mechanical-systems (MEMS) based accelerometer. Repeated ANOVA tests were done between the first pre-test, and the first and second post-tests to assess if there were statistically significant differences between the two groups. Results: There were no statistically significant differences in how the groups performed in terms of punch acceleration and punch force. There were statistically significant increases in mean punch frequencies in the left and right hands, as a result of chiropractic manual manipulation of the cervical spine. Conclusion: Chiropractic manual manipulation of the cervical spine significantly improves punch frequency in boxers. Boxers were, therefore, encouraged to use chiropractic manual manipulation of the cervical spine as a way of improving punch frequency- the maximum number of punches they can deliver to a target in a given unit if time. This may increase their chances of winning in the ring.